A Review of the Renoprotective Effects of Novel Antidiabetic Agents. (February 2021) - Leite, Kelsey M.; Long, Allissa M.; Ostroff, Marissa L.; Borges, Leanna; Braden, Gregory
The objective of this review article was to identify and examine current evidence surrounding the potential renoprotective effects of newer antidiabetic agents such as sodium-glucose cotransporter 2 (SGLT-2) inhibitors, glucose-like peptide 1 (GLP-1) agonists, and dipeptidyl peptidase 4 (DPP-4) inhibitors. A literature search of MEDLINE and PubMed (January 2000 to April 2019) was performed using the following search terms: "diabetes treatment, " "renoprotection, " "kidneys, " "SGLT-2 inhibitors, " "GLP-1 receptor agonists, " "DPP-4 inhibitors, " and the drug names in each of those classes as well as any combination of these terms. Literature was excluded if published in a language other than English, performed in nonhuman subjects, did not include patients from the United States, was nonrandomized, or the data were available from poster presentations. There were 11 studies that met the search criteria. The majority of the studies focused on renal outcomes as secondary end points and looked at albuminuria, estimated glomerular filtration rate changes from baseline, urinary albumin-to-creatinine ratio, serum creatinine, and need for renal replacement therapy. There are fewer studies that focused on renal protection as a primary end point. After reviewing the available literature, the use of SGLT-2 inhibitors and GLP-1 agonists in addition to standard of care may be considered in patients with or at risk of developing chronic kidney disease. SGLT-2 inhibitors and GLP-1 agonists should be considered when patients' diabetes is no longer well controlled with metformin. Other factors such as cost, cardiovascular disease, and other comorbidities may also be taken into consideration when recommending therapy for patients.